Heparinoids and cellular interactions in the vascular system - Preissner, K. T. (Hämostaseologie, 1996)
Heparin and related polysaccharides have long been used for therapautic intervention in different disease states related to thromboembolic complications. The localization and functional availability of heparin-like components in the body is mostly confined to cell surfaces and extracellular matrix/basement membranes. Their strategic position particularly in the vascular system enables heparinoids linked to various core proteins (designated as heparan sulfate proteoglycans) to interact with a variety of heparin-binding proteins such as apolipoproteins, lipases, proteases and protease inhibitors, matrix proteins as well as surface receptors on other cells and microorganisms. The variety in gene expression of respective core proteins and differences in glycosaminoglycan side chains are relevant factors for the selectivity of these interactions. Heparinoid-associated core proteins serve as co-receptors for a number of metabolic properties of vascular cells as well as for the regulation of cellular processes, particular as they relate to cell growth and differentiation in angiogenesis. Moreover, heparan sulfate proteoglycans contribute to the process of lipoprotein retention in the vessel wall and the onset of atherosclerosis. Elucidation of molecular properties, functions and their role in vascular diseases can lead to valuable information for the design of heparinoid analogues to be used for pharmacological intervention.
Keywords: Heparin; heparan sulfate; proteoglycans; co-receptors; endothelial cells; matrix proteins; antithrombin; lipoprotein lipase; atherosclerosis; angiogenesis